Dampak Gerakan Menabung Riang terhadap Perilaku Ekonomi Positif Anak Usia Dini di Desa Buniwangi: Penelitian - Linda Hindriana; Putri Amalia Nurilmi; Lina Agustina; Yusri Algifari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the impact of the “Menabung Riang” (Joyful Saving) movement on positive economic behavior among early childhood in Buniwangi Village. The research employed the Participatory Action Research (PAR) method, engaging children, parents, and stakeholders in active participation. Through various enjoyable educational activities, participants were encouraged to understand the value of saving while fostering healthy financial habits from an early age. Preliminary findings indicate a significant improvement in attitudes and financial behavior, such as consistency in setting aside money and a sense of responsibility in managing resources. These results highlight that participatory and experiential approaches can effectively enhance economic awareness and cultivate constructive financial practices. This study contributes substantially to the development of community-based financial literacy programs that stimulate behavioral transformation from early childhood.